2012
DOI: 10.1007/s10858-012-9674-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell signaling, post-translational protein modifications and NMR spectroscopy

Abstract: Post-translationally modified proteins make up the majority of the proteome and establish, to a large part, the impressive level of functional diversity in higher, multi-cellular organisms. Most eukaryotic post-translational protein modifications (PTMs) denote reversible, covalent additions of small chemical entities such as phosphate-, acyl-, alkyl- and glycosyl-groups onto selected subsets of modifiable amino acids. In turn, these modifications induce highly specific changes in the chemical environments of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
179
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(189 citation statements)
references
References 194 publications
(247 reference statements)
9
179
1
Order By: Relevance
“…S15). Phosphorylation of this Tau441 AT8 protein by RBE leads to a simpler spectrum than for the phosphorylated Tau441-Ser262A protein, albeit with several resonances for each phospho-site because of incomplete phosphorylation (37) (Fig. 5A).…”
Section: P-at8mentioning
confidence: 99%
“…S15). Phosphorylation of this Tau441 AT8 protein by RBE leads to a simpler spectrum than for the phosphorylated Tau441-Ser262A protein, albeit with several resonances for each phospho-site because of incomplete phosphorylation (37) (Fig. 5A).…”
Section: P-at8mentioning
confidence: 99%
“…We analyzed crosstalks that involved the most common PTMs (S/T phosphorylation, K acetylation/methylation), but we have already delineated the NMR characteristics of equally or less abundant PTMs, such as arginine methylation, lysine crotonylation/propionylation, tyrosine phosphorylation. [16] Of outmost importance for the utility of our approach is the ability to prepare specifically and quantitatively modified histones that can be used for asNucs reconstitution. In cases where histone modifications cannot be established enzymatically, alternative schemes for the specific incorporation of modified amino acids can be employed, including non-natural amino acid technologies [17] or the use of cysteine mutant-derived PTM mimetics (histones are devoid of cysteines).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the change in protonation upon acetylation should be the reason for the above unexpected result. Indeed, the change of protonation for nonmodified Lys, as occurs at a high pH value, leads to a  distribution (see Figure S1c Having presented the above test on lysine, we have a validation of our theoretical approach and have shown that computation of the  values, for a given nucleus, is a useful method with which to detect the methylation states of Lys (Theillet et al, 2012a(Theillet et al, , 2012b, but not acetylation (Theillet et al, 2012a). Consequently, we decided to extend this analysis to discuss methylation of Arg, and glycosylation of Ser, Asn and Thr, with model tripeptides, and the results are discussed below.…”
Section: Validation Test On Lysine Derivativesmentioning
confidence: 72%
“…Therefore, perturbation of the pKa upon methylation is not large enough to be used as a probe with which to sense Arg modification. Second, there are other nuclei, than carbons, of the Arg side-chain, such as N  , that show large chemical-shift dispersion upon methylation (Theillet et al, 2012b). However, as noted by Theillet et al (2012b) …”
Section: Methylation Of Argininementioning
confidence: 96%
See 1 more Smart Citation